Research of Folk Piety in Croatian Ethnology: Research Practice in the 19th and the 20th Century and its Infuence on Contemporary Ethnology/Cultural Anthropology - Belaj, Marijana (Array, 2006)
This paper is based on the findings from the research of Croatian folk piety, specifically on the example of the belief in Patron Saints. Folk piety has generally been, and especially in Croatian ethnology, neglected as a research topic. Even though the conceptual ethnographic research and sources from the second half of the 19th and the first half of the 20th century have contained some research of Patron Saints, the data presented were mostly factual and lacked cultural context in which they belonged, or they could be found indirectly, through some other research topics. The material was quantitatively acceptable, but qualitatively inadequate. However, in spite of all the outlined drawbacks, this material, together with the research methodology and concepts through which it was collected, provided us with valuable guidelines for new researches and for the development of analytical categories, which synthesize and explicitly discuss the experiences and processes of contemporary religiousness.